Exploration on drivers’ perception towards traffic inventory performance - Nadia, Arib (2015)
Managing traffic performance is the practice of councils and highway authorities in controlling the use of road network in order to provide safety and achieve efficiency of traffic flow. Often the reliability of traffic performance is neglected when the development of new road evolves over time. However, the significance of road performance cannot be ignored as it involves the safety of road users that cannot be compromised. Therefore, this study is intended to explore drivers’ perception towards traffic inventory performance as well as to suggest basic approach for improving the road. To achieve this, Jalan Kuantan – Gambang was chosen as study location. This study was conducted by using a qualitative study by means of questionnaires distribution. Then the average index method was performed to indicate the driver’s perception towards traffic performance. This study may provide a handy reference to the road authorities and can be used in value engineering appraisal if required by interested party